Analysis of the human alpha-globin gene cluster reveals a highly informative genetic locus. - Higgs, D; Wainscoat, J; Flint, J; Hill, A; Thein, S; Nicholls, R; Teal, H; Ayyub, H; Peto, T; Falusi, A (1986)
Extensive molecular studies have characterized 15 dimorphic and 2 multiallelic genetic markers within the human alpha-globin gene cluster. Analysis of these markers in 9 populations has shown that the alpha-globin locus is remarkably polymorphic and is therefore an ideal marker on chromosome 16 for the construction of a human genetic linkage map. The combined analysis of 9 polymorphic markers has established alpha-globin haplotypes that provide the means to study the molecular genetics and common mutants of this cluster. The novel association of a conventional restriction fragment length polymorphism haplotype and linked, hypervariable regions of DNA should allow a comparison of the rate of change of such markers.